Psychological Well-Being Among Women with Polycystic Ovary Syndrome: Insights from Buug, Zamboanga Sibugay, Philippine - Calanda, Ailyn; Labrador, Hadassah Sulamith; Paracale, Shawie Lou; Tilid, Jhana Marie; Gallego, Randy Ian; Laranjo, Tashmera; Merasol, Hope Lovely (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2026)
Background: Traditionally, Polycystic Ovary Syndrome (PCOS) has been classified primarily as an endocrine disorder. Contemporary research, however, has elucidated its multifaceted nature, encompassing metabolic, hormonal, and psychosocial dimensions that substantially influence patients' quality of life. Women with PCOS are often subjected to significant emotional distress due to the syndrome's physical manifestations, fertility issues, and body image challenges, which are frequently accompanied by elevated levels of anxiety, depression, and stress. This study aims to highlight the psychological ramifications of PCOS diagnosis and underscore the imperative of integrating psychological considerations into holistic patient care.Subjects and Method: Utilizing a descriptive-correlational research design, this study assessed the perceived psychological impact of PCOS diagnosis among women in Buug, Zamboanga Sibugay. A sample of 81 randomly selected respondents completed a validated and reliability-tested questionnaire. The dependent variables comprised the perceived impact of PCOS diagnosis on the respondents’ psychological health. The independent variables of the study were the respondents’ perceptions of their PCOS diagnosis in terms of the duration, challenges, and lifestyle changes associated with the condition. Data were analyzed using Spearman’s rho and Pearson correlation coefficients.Results: The findings indicate that the duration of PCOS diagnosis, the associated challenges, and subsequent lifestyle modifications significantly affect participants' psychological well-being. Statistical analysis indicated significant correlations between psychological health and the duration of diagnosis (p < 0.001), diagnostic challenges (p < 0.001), and lifestyle changes (p < 0.001), highlighting their critical impact on psychological outcomes.Conclusion: The study emphasizes the critical need to incorporate psychological aspects into the management of PCOS. Effective intervention that addresses both the physical and psychological dimensions of PCOS can substantially enhance patient care and improve overall quality of life for women affected by this syndrome.